ANALYZING THE ROLE OF THE KISAN CREDIT CARD (KCC) SCHEME IN REDUCING AGRICULTURAL INDEBTEDNESS AMONG FARMERS - Rawani S.K; Paliwar L.B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper studies the Kisan Credit Card (KCC) scheme and its contribution in reducing agricultural indebtedness of farmers in Jharkhand. As the awareness of rural indebtedness and farmers’ dependence on informal credit sources is mounting, the KCC scheme was designed as an institutional mechanism to provide timely, affordable credit to agricultural needs. The first objective of this research is to determine if the progress of the KCC scheme has reduced farmers’ debt burdens significantly. Structured questionnaires was used to collect data of 385 randomly selected farmers from the region. The SPSS was used to analyze the data and regression analysis was performed to determine the relationship between the independent variable, progress of KCC scheme and the dependent variable, agricultural indebtedness. Results showed statistically significant relationship with an R square value of 0.106 which means that the scheme explains 10.6 percent of the variance in debt levels. The impact is moderate, but it proves that institutional credit from the KCC scheme helps to reduce farmers’ financial stress. The ANOVA results and regression coefficients also show that the scheme has a significant and positive effect. Finally, the KCC scheme is a good tool for rural credit needs and reducing debt but its potential can only be fully realized when other policy measures like improved market access, financial literacy and income stabilization measures are in place. Expanding and strengthening the KCC scheme and other reforms could result in outcome for farmers that are more sustainable yet, suggests the study.